ENHANCING ENGLISH VOCABULARY USING CLT METHOD TOWARD SLB D STUDENTS VIA ZOOM APPLICATION AS INTERACTIVE LEARNING MEDIA - Dini Anggraheni; Anandha Anandha; Hernofika Laksmi T S (Universitas PGRI Semarang, 2020)
The research aims to know-how is the implementation of the CLT method towards English vocabulary. The research objects are special needs students of English Club SLB-D YPAC Semarang. Researchers apply the Communicative Language Teaching method to the students via zoom application. The research objects are six students, applying six materials on seven meetings. The research method used in the research is a descriptive qualitative method. There are four stages of techniques that are used, those are the observation, planning, action, and reflection stages. The results of the study are the students can practice English actively, and gaining new vocabularies during the learning process.